EVALUATION OF THE EUTROPHICATION PHENOMENON IN THE SAGULING DAM WITH A DYNAMIC SYSTEM MODEL - Masrawani
The Saguling Reservoir accommodates various types of waste carried by the Citarum River and its tributaries. The decline in water quality in the Saguling Reservoir is caused by the presence of organic and inorganic materials that enter the reservoir. This study aims to evaluate the eutrophication that occurred in the Saguling Reservoir by looking at the influence of nutrients and biomass of Peridinium sp. The method used in this research is the analysis of water quality, analysis of the load carrying capacity of water pollution which refers to tge Minister of Environment Regulation No. 28 of 2009, and evaluation of the eutrophication phenomenon using STELLA 9.0.2 software with a dynamic system approach. The use of dynamic systems is closely related to the pattern of behavior levels generated by the system over time. The results showed that the number of marine cages in the Saguling Reservoir had exceeded its capacity and when referring to the Minister of Environment Regulation No. 28 of 2009, so now its trophic status has reached the hypereutrophic status. Based on the simulation, the concentration of ammonia, nitrate, and phosphate nutrients is directly proportional to the biomass of Peridinium sp. Peridinium sp biomass increased with increasing nutrient concentration from 2011 to 2030. Ammonia concentration increased from 0,04 mg/L to 0,84 mg/L; nitrate concentration from 1,61 mg/L to 33,81 mg/L; and phosphate concentration from 0,02 mg/L to 0,48 mg/L. After carrying out the scenario of using an aerator, the concentration of ammonia, nitrate, and phosphate nutrients decreased every year; and the harvesting of phytoplankton can reduce nutrient concentration but still exceed the quality standard; and the combination of the two scenarios can reduce the concentration of ammonia, nitrate, and phosphate. This indicates that the addition of aeration and harvesting of phytoplankton in the Saguling Reservoir is very efficient. However, the concentration of phosphate at the time of use of the two scenarios still exceeds the quality standard of PP 22 2021 Class II so that further management is needed.